52 - VIEWS OF SLOVAK ELEMENTARY SCHOOL STUDENTS ON OLYMPIC VALUES (Fiep Bulletin - online, 2023)
Problem Statement: Slovak schools could participate in the educational program created by the International Olympic Committee OVEP (Olympic Values Education Program). It is a program of value education through the values of Olympism, which helps participants develop their positive moral and ethical qualities. The following educational themes, aimed at transmitting a contemporized version of the Olympic principles, are the basis of the OVEP program: joy of effort, fair play, respect for oneself and others, pursuit of excellence, harmonious and balanced life of body, will, and mindApproach: The research sample consisted of 1549 fifth- and sixth-grade students from Slovak elementary schools. The significance of differences in students’ knowledge and attitudes by gender and physical activity was evaluated using the Pearson´s chi-squared test, Mann-Whitney U test and Kruskal-Wallis ANOVA. Purpose: The purpose of the study was to assess the level of knowledge about the ethical values of Olympism among elementary school students and their attitudes to Olympic values.Results: Gender differences in knowledge levels suggest that boys have more knowledge about Olympic values than girls. Significant gender differences in students’ attitudes towards Olympic values were observed for all values, except for friendship. Comparison between groups according to physical activity levels in the students’ knowledge and attitudes showed statistically significant differences in some questionnaire items. Conclusion: The results have shown that gender may be a factor affecting attitudes towards Olympic values. Students achieved a high percentage of correct answers for the knowledge about particular Olympic values, which indicates good levels of knowledge.